2010
DOI: 10.1103/physrevb.81.125116
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the properties of complex transparent conducting oxides: Role of crystal symmetry, chemical composition, and carrier generation

Abstract: The electronic properties of single-and multi-cation transparent conducting oxides (TCOs) are investigated using first-principles density functional approach. A detailed comparison of the electronic band structure of stoichiometric and oxygen deficient In2O3, α-and β-Ga2O3, rock salt and wurtzite ZnO, and layered InGaZnO4 reveals the role of the following factors which govern the transport and optical properties of these TCO materials: (i) the crystal symmetry of the oxides, including both the oxygen coordinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
118
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 75 publications
11
118
0
Order By: Relevance
“…These were done based on first principles DFT calculations combined with the particle swarm optimization algorithm as implemented in the CALYPSO code [36,37]. We also particularly calculated the optical absorption spectra of the compounds when doped [38][39][40]. This is an important but often neglected aspect for identifying transparent conductors.…”
Section: Methodsmentioning
confidence: 99%
“…These were done based on first principles DFT calculations combined with the particle swarm optimization algorithm as implemented in the CALYPSO code [36,37]. We also particularly calculated the optical absorption spectra of the compounds when doped [38][39][40]. This is an important but often neglected aspect for identifying transparent conductors.…”
Section: Methodsmentioning
confidence: 99%
“…The sX-LDA calculated electronic band structures and partial density of states of all single-cation oxides studied in this work have been published earlier [16,17] except for Sc 2 O 3 . The bottom of the conduction band in scandium oxide is governed by the localized Sc d-states, Fig.…”
Section: A Ground State Structuresmentioning
confidence: 99%
“…Recent comparative investigations of main group metal oxides [16,17] have revealed that the fundamental differences in the electronic properties of the conventional TCO hosts (In 2 O 3 , ZnO and CdO) and the light metal oxides (Al 2 O 3 , CaO and MgO) originate from the different energy location of the cation's empty p or d states with respect to the conduction band bottom. In the former oxides, the cation p band is well above its s band which is a prerogative for a good charge transport via a uniform network formed by the spherically symmetric metal s orbitals and the neighboring oxygen p orbitals in degenerately doped materials.…”
Section: A Ground State Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an alternative scheme has been suggested in unconventional TCOs such as Ca 12 Al 14 O 33 , where a defect band crossing the Fermi level was suggested to be the source of conductivity in this very wide band gap material [179]. A recent first-principles investigation by Medvedeva and Hettiarachchi [180] into single-and multi-component TCOs has also identified a number of microscopic properties, such as the overlap of metal s-states with oxygen p-states, oxygen coordination, and the doping with transition metal elements, which could be important to effectively obtain high conductivity material while maintaining optical transparency.…”
Section: Overriding Explanation?mentioning
confidence: 99%